Space vacation [videorecording (DVD)] - Russell, Dan (Narrator) (NGHT, Inc., 2011)
"Space: the final frontier for an out-of-this-world vaction. Space tourism will literally revolutionize our view of the world, and some of the world's leading scientists and engineers are working at light speed to bust the industry wide open. through the eyes of space visionaries, glimpse future space resorts with panoramic views of all the world's oceans, giant inflatable space hotels, and spacecraft that may one day travel through worm holes to distant galaxies"--Container.